Differentiated umbilical cord matrix stem cells as a new in vitro model to study early events during hepatitis B virus infection1. Issue 1 (7th January 2013) - Paganelli, Massimiliano; Dallmeier, Kai; Nyabi, Omar; Scheers, Isabelle; Kabamba, Benoît; Neyts, Johan; Goubau, Patrick; Najimi, Mustapha; Sokal, Etienne M.
Abstract The role of cell differentiation state on hepatitis B virus (HBV) replication has been well demonstrated, whereas how it determines cell susceptibility to HBV entry is far less understood. We previously showed that umbilical cord matrix stem cells (UCMSC) can be differentiated towards hepatocyte‐like cells in vitro. In this study we infected undifferentiated (UD‐) and differentiated (D‐) UCMSCs with HBV and studied the infection kinetics, comparing them to primary human hepatocytes (PHHs). UD‐UCMSCs, although permissive to viral binding, had a very limited uptake capacity, whereas D‐UCMSCs showed binding and uptake capabilities similar to PHHs. Likewise, asialoglycoprotein receptor (ASGPR) was up‐regulated in UCMSCs upon differentiation. In D‐UCMSCs, a dose‐dependent inhibition of HBV binding and uptake was observed when ASGPR was saturated with known specific ligands. Subsequent viral replication was shown in D‐UCMSCs but not in UD‐UCMSCs. Susceptibility of UCMSCs to viral replication correlated with the degree of differentiation. Replication efficiency was low compared to PHHs, but was confirmed by (1) a dose‐dependent inhibition by specific antiviral treatment using tenofovir; (2) the increase of viral RNAs along time; (3) de novo synthesis of viral proteins; and (4) secretion of infectious viral progeny. Conclusion: UCMSCs become supportive of the entire HBV life cycle upon in vitro hepatic differentiation. Despite low replication efficiency, D‐UCMSCs proved to be fully capable of HBV uptake. Overall, UCMSCs are a unique human, easily available, nontransformed, in vitro model of HBV infection that could prove useful to study early infection events and the role of the cell differentiation state on such events. (HEPATOLOGY 2013)